2023
DOI: 10.1071/wf22206
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Wildland Fire Decision Support System (WFDSS) for full suppression and managed fires within the Southwestern Region of the US Forest Service

Abstract: Background. United States federal wildland fire policy requires the use of formal decision support systems (DSS) for fire incidents that last for an extended time. However, the ways that wildfire managers use DSSs in decisions regarding fire management remain understudied, including how users engage with or utilise them to make strategic decisions. Aims. Researchers sought to understand how users engage with the Wildland Fire Decision Support System (WFDSS), their view of its utilities and challenges, and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Studies that have examined the Wildland Fire Decision Support System (WFDSS), a tool developed expressly to guide decisions on federal lands, have shown that rather than being part of the actual decision process, it is most often used to document cognitive decisional processes. However, tools embedded within WFDSS were shown to be useful to validate any a priori assumptions or to examine alternative scenarios (Noble and Paveglio 2020;Rapp et al 2020;Fillmore and Paveglio 2023). Other studies have employed 'choice set' surveys that present decision makers with multiple alternatives to choose from to determine their risk preferences.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Studies that have examined the Wildland Fire Decision Support System (WFDSS), a tool developed expressly to guide decisions on federal lands, have shown that rather than being part of the actual decision process, it is most often used to document cognitive decisional processes. However, tools embedded within WFDSS were shown to be useful to validate any a priori assumptions or to examine alternative scenarios (Noble and Paveglio 2020;Rapp et al 2020;Fillmore and Paveglio 2023). Other studies have employed 'choice set' surveys that present decision makers with multiple alternatives to choose from to determine their risk preferences.…”
Section: Research Backgroundmentioning
confidence: 99%
“…These studies found that successful coordination of response was driven by prefire planning that allowed the establishment of relationships and communication channels (Owen et al 2012;Nowell and Steelman 2015). The use of decision support systems (DSS) to navigate operational decision-making in the Southwest is increasingly documented by social scientists, revealing specific benefits for oversight of natural ignitions to achieve management objectives when using the Wildland Fire Decision Support System (WFDSS) (Fillmore and Paveglio 2023) and capacity for refocusing on long-term land management strategies when using Potential Operational Delineations (PODs) (Greiner et al 2021).…”
Section: Wildfire Responsementioning
confidence: 99%